2010
DOI: 10.1007/s11746-010-1630-x
|View full text |Cite
|
Sign up to set email alerts
|

Shelf Life of Cold‐Pressed Pumpkin (Cucurbita pepo L.) Seed Oil Obtained with a Screw Press

Abstract: The production of cold-pressed oil from nonroasted naked pumpkin seeds by pressing with screw presses started in the Republic of Serbia at the end of 1990s. This oil has the characteristic flavour of raw-dried seeds, and is a specific product of this region. The oil samples were prepared by pressing naked pumpkin seeds and pumpkin seeds with the hulls in a 3:2 ratio using a screw press. The changes of the oil sensory characteristics, basic chemical quality and oxidative stability were followed over a 2-year pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
41
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 19 publications
7
41
0
1
Order By: Relevance
“…This was later confirmed by Tassan et al (2011) and Abdellah and Ahmed Ishag (2012) who observed significant changes in physical and chemical characteristics of sunflower oil, both in stored oil and in fresh oil extracted from stored seeds, irrespective of the extraction method. Similar observations have been reported by Rao (2008) with stored Jatropha seed oil and by Vujasinovic et al (2010) with pumpkin seed oil.…”
Section: Introductionsupporting
confidence: 91%
“…This was later confirmed by Tassan et al (2011) and Abdellah and Ahmed Ishag (2012) who observed significant changes in physical and chemical characteristics of sunflower oil, both in stored oil and in fresh oil extracted from stored seeds, irrespective of the extraction method. Similar observations have been reported by Rao (2008) with stored Jatropha seed oil and by Vujasinovic et al (2010) with pumpkin seed oil.…”
Section: Introductionsupporting
confidence: 91%
“…Due to their specific and positive health effects, there are several studies on pumpkin seed cultivars in different countries which assess the content of bioactive compounds. Vujasinovic et al, (2010) reported the sensory properties, quality characteristics and oxidative stabilities of screw-pressed pumpkin (Cucurbita pepo L.) seed oils. The contents of essential fatty acids in the oil samples were determined as 30.35-42.07% for oleic and 43.68-52.15% for linoleic acid, and 0.16-0.26% for linolenic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, this oil is used as a salad oil in several countries (Austria, Slovenia and Hungary), due to its pleasant sensory properties, high nutritive value and good oxidative stability, as it has a high content of natural antioxidants, such as phenolic compounds (Tsaknis et al, 1997;Murković et al, 2004;Yu et al, 2005;Stevenson et al, 2007;Fruhwirth and Hemetter, 2008;Vujasinovic et al, 2010). Moreover, this oil has gained attention, not only as an edible oil, but also as a potential nutraceutical.…”
Section: Introductionmentioning
confidence: 99%